Tracing the Threads: Comparing Red Garments in Forensic Investigations - Jolanta Wąs-Gubała; Bartłomiej Feigel (Applied Sciences, 2025)
The aim of this study was to compare the types, textile structures, labels, and fiber compositions of 64 red garments submitted as evidence in selected criminal cases between 2022 and 2024. The research enhanced the current knowledge of the characteristics of red clothing available to consumers and demonstrated the relevance of textile analysis in forensic science. Knitted fabrics were the most commonly used in the garments, followed by woven fabrics, nonwovens, and felts. Fiber identification focused on color and shade, generic classification, morphological structure, and chemical composition, revealing both similarities and distinctions among the samples. In a small percentage of cases, label information was found to be inaccurate. The study also examined the fiber content of threads, patches, logos, prints, and embroidery, underscoring the forensic potential of these often-overlooked elements. The identification of over 300 individual fibers enabled a critical evaluation of the analytical procedures and confirmed their effectiveness in forensic contexts.